Discrepancy between early neurological course and mid-term outcome in older stroke patients after mechanical thrombectomy. (5th June 2015) - Kleine, Justus F; Boeckh-Behrens, Tobias; Prothmann, Sascha; Zimmer, Claus; Liebig, Thomas
Abstract : Background: Stroke in aged patients has a relatively poor prognosis, even after recanalizing therapy. Potential reasons include mechanisms that relate directly to the extent of brain tissue damage, but also age-dependent factors which are not, or only indirectly, stroke-related, such as pre-existing functional deficits, comorbidities, and post-stroke complications (eg, infections). Objective: To compare early neurological course with subsequent functional outcome in older (≥80 years) and younger stroke patients in order to estimate the relative impact of these factors. Specifically, to examine if the strong age-dependency of modified Rankin Scale (mRS) outcome scores in stroke patients after mechanical thrombectomy is paralleled by a similar age dependency of early postinterventional National Institute of Health Stroke Scale (NIHSS) scores—a more specific measure of stroke-induced brain damage. Methods: We evaluated technical results, pre- and postinterventional NIHSS scores, mid-term mRS scores and early and overall mortality and their relation to age in 125 patients, 40 of them ≥80 years, with acute middle cerebral artery occlusion, treated by mechanical thrombectomy. Results: Technical success, pre- and postinterventional NIHSS scores and early mortality were age-independent. Early neurological improvement depended on successful recanalization, but not on age. Nevertheless, good mRS outcome (mRS 0–2) was much rarer, and overall mortality almost threefold higher in aged patients. Conclusions: Older patients exhibit a similar early neurological course and responsiveness to mechanical thrombectomy as younger patients, but this is not reflected in mid-term functional outcome scores. This indicates that post-stroke complications and other factors that are not, or only indirectly, related to the brain tissue damage induced by the incident stroke have a dominant role in their poor prognosis.